1987
DOI: 10.1016/0014-5793(87)81220-6
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum neurotoxin inhibits depolarization‐stimulated protein phosphorylation in pure cholinergic synaptosomes

Abstract: Botulinum neurotoxin, a strong blocker of acetylcholine release at peripheral cholinergic synapses, inhibits depolarization-stimulated protein phosphorylation in pure cholinergic synaptosomes isolated from the electric organ of Torpedo marmorata. Moreover, tetrodotoxin has the same effect on protein phosphorylation when cholinergic synaptosomes are depolarized by veratridine. Correlation between presynaptic protein phosphorylation and acetylcholine release is suggested by the fact that botulinum neurotoxin blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1988
1988
1994
1994

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…However, the fact that selective inhibition of calcium-activated SV cycling results in major changes of the phosphoproteome documents that the activation status of the kinase/phosphatase networks is directly dependent on the progression of the exoendocytotic cycle. In most cases, BoNT treatment inhibited phosphorylation, and these results are in line with a very early study that used BoNT-treated synaptosomes from the electric organ of Torpedo marmorata and radioactive phosphate for protein labeling (390).…”
Section: Discussionsupporting
confidence: 84%
“…However, the fact that selective inhibition of calcium-activated SV cycling results in major changes of the phosphoproteome documents that the activation status of the kinase/phosphatase networks is directly dependent on the progression of the exoendocytotic cycle. In most cases, BoNT treatment inhibited phosphorylation, and these results are in line with a very early study that used BoNT-treated synaptosomes from the electric organ of Torpedo marmorata and radioactive phosphate for protein labeling (390).…”
Section: Discussionsupporting
confidence: 84%
“…Effects of phorbol esters have also large quantity of cholinergic synaptosomes can be obtained from it. In recent studies we have shown a likely relationship between neurotransmitter release and protein phosphorylation in these synaptosomes (Guitart et al, 1987). On the other hand, botulinum toxin (BoTx), a strong blocker of peripheral cholinergic transmission (Simpson, 1986), has been shown to impair the quanta1 release of neurotransmitter in the electric organ of Torpedo (Dunant et al, 1987) and to inhibit specifically the potassium-induced release of ACh from Torpedo electric organ synaptosomes .…”
mentioning
confidence: 99%